Evaluation of the Inhibitory Effects of Lactobacillus gasseri and Lactobacillus crispatus on the Adhesion of Seven Common Lower Genital Tract Infection-Causing Pathogens to Vaginal Epithelial Cells - He, Yuanhui; Niu, Xiaoxi; Wang, Ben; Na, Risu; Xiao, Bingbing; Yang, Huixia (Frontiers in Medicine, 2020)
Background/purpose: Lactobacillus colonization is important to maintain urogenital flora stability and prevent pathogenic infection. Different Lactobacillus species have distinct properties and effects on the urogenital flora. To select probiotics that colonize the vagina and provide protection against pathogenic infection, we evaluated the adhesion of five Lactobacillus strains and their inhibitory effects on the adhesion of pathogens to vaginal epithelial cells (VECs). Methods and materials: 1) Lactobacillus adhesion experiments: VK2/E6E7 and primary VECs were used to evaluate the adhesion of two Lactobacillus gasseri and three Lactobacillus crispatus strains. The adhesion of these five Lactobacillus strains was compared. 2) Adhesion inhibition experiments: The inhibitory effects of the five Lactobacillus strains on the adhesion of pathogens (Gardnerella, Mobiluncus, Candida albicans, Streptococcus agalactiae, Staphylococcus aureus, Escherichia coli, and Enterococcus faecalis) were evaluated by adhesion exclusion, displacement, and competition experiments. Results: 1) Lactobacillus adhesion was stronger in the primary VECs than in the VK2/E6E7 VECs (P <0.05). The adhesion of the three L. crispatus strains was stronger than that of the two L. gasseri strains (P <0.05). L. crispatus 4# showed the strongest adhesion. 2) The exclusion, displacement, and competition experiments showed that all five Lactobacillus strains significantly inhibited the adhesion of the seven pathogenic strains to the VECs (P <0.05). The displacement effect was stronger than the exclusion and competition effects of each Lactobacillus strain. 3) The results of the exclusion, displacement, and competition experiments indicated that L. gasseri 1# showed the strongest adhesion inhibition of C. albicans and S. agalactiae. L. crispatus 3# showed the strongest adhesion inhibition of S. aureus, whereas L. crispatus 4# showed the strongest adhesion inhibition of Gardnerella, Mobiluncus, E. coli, and E. faecalis. Conclusion: The source of the VECs might not affect the selection of the most adhesive Lactobacillus strain. L. crispatus showed stronger VEC adhesion than L. gasseri. The degree of antagonism of the Lactobacillus strains toward the different pathogens varied. This result provides incentives for personalized clinical treatment.